2014
DOI: 10.1002/jbm.b.33104
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified poly(2‐hydroxyethyl methacrylate) cryogel for the adsorption of heparin

Abstract: Various clinical procedures, such as cardiovascular surgery or extracorporeal blood purification, involve systemic anticoagulation using heparin. High concentrations of circulating heparin require neutralization due to possible serious bleeding complications. The intravenous administration of the heparin antagonist protamine sulfate is routinely clinically performed, but is frequently associated with adverse reactions. Therefore, there is a need for a valid and safe alternative to achieve extracorporeal hepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Under the same conditions, the non-specific adsorption of heparin onto the bare poly(2-hydroxyethyl methacrylate) cryogel was 8% of the initial amount. They reported that the composite cryogels showed good blood compatibility, as indicated by negligible adsorption of albumin, anti-thrombin III, and total protein, thus, it is suitable for extracorporeal heparin removal [59].…”
Section: Composite Cryogels As Versatile Tools For Biomedical Applmentioning
confidence: 99%
“…Under the same conditions, the non-specific adsorption of heparin onto the bare poly(2-hydroxyethyl methacrylate) cryogel was 8% of the initial amount. They reported that the composite cryogels showed good blood compatibility, as indicated by negligible adsorption of albumin, anti-thrombin III, and total protein, thus, it is suitable for extracorporeal heparin removal [59].…”
Section: Composite Cryogels As Versatile Tools For Biomedical Applmentioning
confidence: 99%
“…Our results confirmed the good reusability and stability of the HNT–NR 3 + , prepared in this paper and reveal that this adsorbent can be easily recovered utilizing saturated NaCl. Furthermore, reported absorbents for heparin recovery, such as chitosan, ,, activated carbon, hydroxyapatite, and polymer-based materials, , tend to be costly. HNTs have notable benefits relative to other adsorbents in that they are inexpensive and easily obtained, as well as being environmentally friendly and biocompatible.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the cumulative release of 5-FU decreased by the increasing amount of cross-linker, and 5-FU transport mechanism was found to be non-Fickian. In another study, Çetin et al prepared an implantable and degradable molecularly imprinted cryogel for pH-responsive delivery of doxorubicin (DOX) [36]. The release rate of DOX from cryogel discs increased in more acidic conditions.…”
Section: Controlled Drug Deliverymentioning
confidence: 99%